Simultaneous measurement of refractive index and temperature based on tapered no-core fiber cascaded with a fiber Bragg grating - Yushan Liu; Song Xie; Yuanyuan Zheng; Xiaozhan Yang (Results in Optics, 2022)
A Mach-Zehnder interference fiber-optic sensor for simultaneous measurement of temperature and refractive index (RI) is proposed and fabricated. In the sensing structure, no-core fiber (NCF) is cascaded with fiber Bragg grating (FBG), two enlarged tapers between NCF and the single-mode fiber serve as the light coupler, and the shrinked taper between two NCFs is used to enhance the interference effect. The different diameter influence of the shrinked taper on the sensing performance of RI and temperature has been evaluated, and the optimum diameter has been obtained. By monitoring the wavelength shift of FBG and the interference dip in the transmission spectra, the simultaneous measurement of temperature and RI is achieved. The maximum sensitivities of the attenuation peak to RI and temperature are 201.7157 nm/RIU and 87.4 pm/°C, respectively. The sensitivities of FBG to RI and temperature are 80.6 pm/RIU and 13.5 pm/°C, respectively. The transformation matrix has also been given. Own to the simple fabrication and high sensitivity, the sensor has the potential application in simultaneous measurement of multiple parameters.